Tibiopedal Access for Crossing of Infrainguinal Artery Occlusions: A Prospective Multicenter Observational Study. (December 2016) - Walker, Craig M.; Mustapha, Jihad; Zeller, Thomas; Schmidt, Andrej; Montero-Baker, Miguel; Nanjundappa, Aravinda; Manzi, Marco; Palena, Luis Mariano; Bernardo, Nelson; Khatib, Yazan; Beasley, Robert; Leon, Luis; et al.
Purpose: To report a prospective, multicenter, observational study ( ClinicalTrials.gov identifier NCT01609621) of the safety and effectiveness of tibiopedal access and retrograde crossing in the treatment of infrainguinal chronic total occlusions (CTOs).Methods: Twelve sites around the world prospectively enrolled 197 patients (mean age 71±11 years, range 41-93; 129 men) from May 2012 to July 2013 who met the inclusion criterion of at least one CTO for which a retrograde crossing procedure was planned or became necessary. The population consisted of 64 (32.5%) claudicants (Rutherford categories 2/3) and 133 (67.5%) patients with critical limb ischemia (Rutherford category ≥4). A primary antegrade attempt to cross had been made prior to the tibiopedal attempt in 132 (67.0%) cases. Techniques used for access, retrograde lesion crossing, and treatment were at the operator's discretion. Follow-up data were obtained 30 days after the procedure.Results: Technical tibiopedal access success was achieved in 184 (93.4%) of 197 patients and technical occlusion crossing success in 157 (85.3%) of the 184 successful tibial accesses. Failed access attempts were more common in women (9 of 13 failures). The rate of successful crossing was roughly equivalent between sexes [84.7% (50/59) women compared to 85.6% (107/125) men]. Technical success did not differ significantly based on a prior failed antegrade attempt: the access success rate was 92.4% (122/132) after a failed antegrade access vs 95.4% (62/65) in those with a primary tibiopedal attempt (p=0.55). Similarly, crossing success was achieved in 82.8% (101/122) after a failed antegrade access vs 90.3% (56/62) for patients with no prior antegrade attempt (p=0.19). Minor complications related to the access site occurred in 11 (5.6%) cases; no patient had access vessel thrombosis, compartment syndrome, or surgical revascularization.Conclusion: Tibiopedal access appears to be safe and can be used effectively for the crossing of infrainguinal lesions in patients with severe lower limb ischemia.